EFEKTIVITAS SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DI BIRO UMUM SEKRETARIAT DAERAH PROVINSI SULAWESI TENGAH - Nur Rosalia Juita Tahwali; Umi Kalsum; Darmawati Darmawati; Dewi Hastuty; Muh Nawawi; Dandan Haryono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The Integrated Dynamic Information and Archive System application abbreviated as SRIKANDI is an electronic correspondence application that aims to be papperless. The purpose of this study was to determine the application of the SRIKANDI application and determine the level of effectiveness of its application. The research method used is descriptive qualitative with purposive sampling data collection techniques with data analysis techniques including; data collection, data condensation, data presentation, and conclusion drawing / data verification. The results showed that there were obstacles that affected the effectiveness of using the SRIKANDI application at the General Bureau of the Regional Secretariat of Central Sulawesi Province so that the acceleration of the use of the SRIKANDI application was hampered and had not achieved the main objectives of implementing the SRIKANDI application.